Development of a Supply Chain Technique for Identifying Border Supporting Cities in the Analysis of Processes of Inter-regional Spatial Integration - S. I Lilimberg; Y. A Nechayeva (International Journal of Supply Chain Management, 2020)
Abstract- Inter-regional spatial integration contributes to supply chain activities for the solution of economic, environmental, socio-demographic, humanitarian and other problems of border areas through the implementation of inter-regional programs and projects. A major role in the development of integration processes is played by border supporting cities. Most researchers, characterizing the main criteria for the selection of supporting cities, call the geographical location, administrative independence, the level of development of urban infrastructure. This study examines the author's systematic approach to the development of criteria for assessing border supporting cities. The purpose of the study is to develop a supply chain strategy for classifying border cities as supporting and indicators for assessing their development level. The main research methods were the analytical, monographic, statistical methods, the score method, as well as the sum of places method (rating method) for conducting an aggregate assessment of the potential of integration cooperation. The authors of the study developed a supply chain methodology for identifying border supporting cities based on a systematic approach that takes into account economic and social indicators for assessing border cities. The results of testing the proposed methodology on the example of the Kazakh-Russian borderland showed that the border city, with a population of over 100 thousand people and located on the border territory, is or can in the future become a reference if there is an appropriate transport and geographical location and cross-border and integration cooperation potential. The application of this technique will allow in the future to increase the efficiency of regulation and management of interregional spatial integration processes.